The impact of poverty alleviation through relocation on loneliness among older adults: the mediating role of social networks and the moderating role of support policies - Li, Chuan; Zhong, Ruoxi; Chen, Hao; Liu, Yunwei (Frontiers in Psychology, 2026)
IntroductionPoverty Alleviation through Relocation (PAR) aims to break the intergenerational transmission of poverty by improving living environments. Understanding its impact on the psychological well-being of older adults, particularly loneliness, holds significant value for refining post-relocation support policies, enhancing the welfare of older populations, and promoting active aging.MethodsThis study utilizes 2025 field survey data from Sichuan, Yunnan, and Guizhou provinces. The analysis employs an instrumental variable approach to address endogeneity, a mediation effect model to test the role of social exchange intensity, and a moderation effect model to examine the buffering effect of support policies.ResultsFindings indicate that PAR significantly associated with higher overall levels of loneliness among older adults. (β = 0.568, p < 0.01). However, PAR exerts differential effects on distinct dimensions of loneliness: it significantly aggravates emotional loneliness (β = 3.592, p < 0.01) while alleviating social loneliness (β = −1.486, p < 0.01). Heterogeneity analysis further reveals that the vulnerability to loneliness is more prominent among older adults in centralized resettlement communities and those in the older-old age group. Mechanism analysis suggests that social exchange intensity mediates the effect of PAR on loneliness. Support policies effectively mitigate the negative impact of PAR on emotional loneliness.DiscussionThis study reveals that while PAR improves material conditions, it may simultaneously create structural risks for the psychological well-being of older adults by disrupting social networks and weakening emotional support. The study recommends building differentiated psychological support systems, strengthening mechanisms for social network reconstruction, improving targeted support for vulnerable groups, and integrating mental health services into community governance. These measures can systematically enhance the psychological well-being of older adults in PAR communities.